Temperature Regime of Water in the Near Shore Zone of the Reservoir of the Vilyuysk Hydroelectric Power Station (Temperaturnn Vody v Prkbrejnoy Zone Vodokhranilisha, Viliuiskoy Ges). - Konstantinov,I P (1977)
The thermal effect of water on frozen soil is one of the important factors involved in the reformation of the shore of artificially constructed reservoirs in areas where permafrost soil occurs. This report details the observations associated with the formation of the shores of the Vilyuysk Reservoir and the monitoring of water temperature. (Author) Trans. of Kolyma, (USSR) v40 p32-34 Feb 76.